Interface slip model for reinforced concrete columns strengthened with concrete jacketing - Caglar, Naci; Sichko, Alexander; Sezen, Halil; Bicici, Erkan; Demir, Aydin; Farhan Farah, Ahmad (Revista de la Construcción. Journal of Construction, 2020)
Retrofit and rebuilding are two potential solutions for reinforced concrete (RC) structures with columns that have insufficient detailing or strength to withstand seismic loads or other extreme events. Demolition and rebuilding can be expensive and time-consuming. Thus, retrofitting and strengthening of columns can be an efficient solution. Jacketing of reinforced concrete columns is one of the common methods for retrofit and rebuilding. For jacketing method, the main concern is the performance loss between new and old concrete due to interface slip. There are three major options to provide a better performance, as surface roughening, dowels, and both. In this study, the methods to provide coworking of new and old concrete are evaluated with respect to four parameters; strength, energy dissipation, stiffness, and displacement ductility. Additionally, a slip coefficient is proposed to model the friction between new and old concrete. The proposed model is applied into OpenSees and a Finite Element (FE) software. The slip coefficient is simulated numerically by a friction coefficient using a tangential contact behavior definition as well. Finally, a slip coefficient is proposed for each method.